Influential Article Review - Twitter as A Communication Channel for Scientists - Washington, Harold; Hughes, Joan; Baker, Ryan (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation. We present insights from a highly influential paper. Here are the highlights from this paper: There have been strong calls for scientists to share their discoveries with society. Some scientists have heeded these calls through social media platforms such as Twitter. Here, we ask whether Twitter allows scientists to promote their findings primarily to other scientists (“inreach”), or whether it can help them reach broader, non-scientific audiences (“outreach”). We analyzed the Twitter followers of more than 100 faculty members in ecology and evolutionary biology and found that their followers are, on average, predominantly (∼55%) other scientists. However, beyond a threshold of ∼1000 followers, the range of follower types became more diverse and included research and educational organizations, media, members of the public with no stated association with science, and a small number of decision-makers. This varied audience was, in turn, followed by more people, resulting in an exponential increase in the social media reach of tweeting academic scientists. Tweeting, therefore, has the potential to disseminate scientific information widely after initial efforts to gain followers. These results should encourage scientists to invest in building a social media presence for scientific outreach. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.